KONTRADIKSI AL-QURAN DAN HADIST - Ihsan Satrya Azhar (Jurnal Al-Fatih, 2018)
In the principles of islamic Jurisprudence (Ushul Alfiqh) The Conflict of proofs (ta’arudl) can be terminated by using some procedures; activating use of all proofs (I’malu Dalilain) with collecting(al-jam’u) or adjusment of two proofs (taufiq) or specification (takhsis) or restricting the absolute word (taqyid) or explanation/clarification of global statement (bayan al-mujmal); activating use of one proof (I’malu ihda dalaail) with abrogation (nasakh) or preferring (tarjih) ; pending use of all proofs (tawaqquf) or aborting use of all proofs (tasaquth). But when, particularly, the indication meaning (dilalah) of Alquran and the indication meaning (dilalah) of Hadist contradict, and when all prosedures above are useless, it would be preferred the indication meaning (dilalah) of Hadist to meet with the the indication meaning (dilalah) of Alquran.